OEIS complex: rare combination of congenital malformations in Aracaju-Sergipe: rare combination of congenital malformations, in Aracaju-Sergipe - Sandes, Maylla Fontes (2021)
OEIS complex is a set of congenital malformations that includes spinal defects, omphalocele, imperforate anus and bladder exstrophy. It is a rare condition, presenting an estimated occurrence in 1:200.000 to 1:400.000 pregnancies. it is not an easily diagnosed pathology during prenatal, and most of the cases result in the death of the fetus. Its etiology is still uncertain and little known and probably multifactorial. The prognosis of these patients are directly related with the severity of the malformations presented and with the quality of the prenatal. The multidisciplinary approach is of importance, as well as the family’s support.